Research on Modification Method of Internal Gearing Power Honing based on Flexible Dressing of Honing Wheel - Lian Xia; Qing Wang; Jiang Han; Xiaoqing Tian (Jixie chuandong)
In order to process the workpiece with internal gearing power honing technology，the honing wheel is usually dressed with the customized diamond dressing wheel corresponding to the workpiece. A method of internal gearing power honing modification based on flexible dressing of honing wheel is proposed to increase the commonality of diamond dressing wheel，reduce the cost of internal gearing power honing technology. Firstly，the tooth surface mathematical model of dressing and honing is established according to the motion relationship of each axis of gear honing machine. Then，the multi axis linkage of honing wheel dressing is expressed in polynomial form，the influence of each axis movement on the final workpiece tooth surface is expressed as sensitivity matrix，and the polynomial coefficients of each axis are optimized with the target modification tooth surface. Finally，the final tooth surface of the workpiece is calculated according to the optimized motion parameters of honing，and the tooth contact is analyzed. The results show the standard diamond dressing wheel can be used for flexible dressing of honing wheel，and the effective modification workpiece can be machined finally.